2017
DOI: 10.1371/journal.pone.0182997
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant action of low, physiologic, and high albumin levels in whole blood

Abstract: Albumin is the most abundant plasma protein. Critical illness is often associated with altered, predominately decreased, serum albumin levels. This hypoalbuminaemia is usually corrected by administration of exogenous albumin. This study aimed to track the concentration-dependent influence of albumin on blood coagulation in vitro. Whole blood (WB) samples from 25 volunteers were prepared to contain low (19.3 ± 7.7 g/L), physiological (45.2 ± 7.8 g/L), and high (67.5 ± 18.1 g/L) levels of albumin. Haemostatic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 49 publications
1
100
0
2
Order By: Relevance
“…Several previous studies suggest that albumin affects blood coagulation system. Pear M et al revealed significant anticoagulant properties of albumin in vitro [36]. According to this study, albumin inhibits the deposition of platelets in the primary hemostasis and impairs fibrinogen activity by interacting with fibrinogen [36].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several previous studies suggest that albumin affects blood coagulation system. Pear M et al revealed significant anticoagulant properties of albumin in vitro [36]. According to this study, albumin inhibits the deposition of platelets in the primary hemostasis and impairs fibrinogen activity by interacting with fibrinogen [36].…”
Section: Discussionmentioning
confidence: 66%
“…Pear M et al revealed significant anticoagulant properties of albumin in vitro [36]. According to this study, albumin inhibits the deposition of platelets in the primary hemostasis and impairs fibrinogen activity by interacting with fibrinogen [36]. Maclouf J et al showed that albumin inactivates thromboxane A2, which is capable of inducing platelet aggregation, directly through binding [37].…”
Section: Discussionmentioning
confidence: 83%
“…The role of albumin in terms of blood coagulation is controversial. In vitro, low albumin level increased ROTEM maximum clot firmness [32]. On the other hand, extreme dilution with albumin is associated with coagulopathy in TEG [33].…”
Section: Discussionmentioning
confidence: 88%
“…However, Sivaraman and Lautour [24] proposed that in its adsorption state, serum albumin changes the structure of a large number of charged amino acids (i.e., 24 arginine, 59 lysine, 35 aspartic acid, and 62 glutamic acid residues) recognized by Arg-Gly-Asp (RGD)-specific receptors in platelets similar to an RGD motif. In addition, studies have reported that serum albumin shows significant anticoagulant action in a concentration-dependent manner [26]. According to this theory, serum albumin that remained in platelet pellets produced by centrifugation might be able to support initial platelet adhesion in collaboration with other genuine adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%